2019
DOI: 10.1080/14999013.2018.1532972
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Ward Social Climate, Ward Sense of Community, and Incidents of Disruptive Behavior: A Study of a High Secure Psychiatric Sample

Abstract: The relationship between ward social climate, ward sense of community and incidents of disruptive behaviour: A study of a high secure psychiatric sample

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Patients have reported that coercion is applied in a disproportionate way not only in terms of individual measures but to the system as a whole ( 93 ). A correlation has been found between disruptive behaviour, violence, and seclusion use in relation to sense of community and ward climate ( 109 ).…”
Section: Reducing Coercion and Restrictive Practisesmentioning
confidence: 99%
“…Patients have reported that coercion is applied in a disproportionate way not only in terms of individual measures but to the system as a whole ( 93 ). A correlation has been found between disruptive behaviour, violence, and seclusion use in relation to sense of community and ward climate ( 109 ).…”
Section: Reducing Coercion and Restrictive Practisesmentioning
confidence: 99%
“…Routine outcomes are used to assess effectiveness within inpatient forensic services ( 15 ). At a service level, outcome data include length of stay ( 16 ), discharge rates ( 17 ), movement between levels of security ( 15 ), frequency of inpatient violence ( 18 ), and incidents of disruptive behavior ( 19 ). At a service user level, risk assessments, such as the HCR-20v3, are used to index treatment progression ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, more recent understandings have emphasised the importance of environmental factors and more specifically, their complex interactions with these patient-related factors 15 16. Thus, recent efforts to understand violence in psychiatric settings have been far more diverse in their scope, and have sought to identify how violence is influenced by (among other factors), the physical environments of wards,17 nurse and patient interpersonal styles,18 ward social climate and sense of community,19 and coercive measures 15. Perhaps most comprehensive in this respect is Cutcliffe’s and Riahi’s15 16 systemic model of variables that contribute to aggression and violence, which incorporates phenomena related to the environment, individual patients, individual clinicians and a mental healthcare system in its entirety.…”
Section: Introductionmentioning
confidence: 99%